Auditoría financiera: aplicación para la elaboración del presupuesto dentro del sindicato de choferes de Pasaje - Torres Ortiz, Jessenia Esperanza (2017)
(Rueda Galvis, 2011) Business success lies in the correct formation of the income and expenses that will be generated during an economic period, this action is called budgeting. The discipline of the budget projects values with respect to the economic and financial movement of future years, and expresses an idea to the managers of situations through which the entity will cross during the included periods. (Muñoz Santiago, 2010) Incorrect evaluation of a budget leads to inefficient decisions and misallocation of monetary resources, being the starting point for the economic deficit and institutional failures. In preparing the financial statements of subsequent years, those responsible should cover those uncertainties that revolve around their economic activity, it is also necessary to provide a financial cushion in case of omitting any irregularities. By applying an audit, we will serve as a basis for analysis by discovering the main irregularities in financial forecasts, including detecting gaps in our policies, making it difficult to achieve stated objectives. Having said this, there is a need to study the budget phase of the Professional Passenger Drivers Union, determining how accurate is their projection towards the future and the correct drafting of a manual that will provide their employees with the actions to be performed to achieve objectives.